User requirement evaluation of channel coding schemes for 5G mobile communication system in transmitting short length messages - Hajiyat, Zahraa Raad Mayoof (2019)
The fifth-generation (5G) communication system begins in the year 2020. Based on different user requirements, the 5G setting includes three scenarios; Enhanced Mobile Broadband (eMBB), Ultra-Reliable Low-Latency Communication (URLLC), and massive Machine-Type Communication (mMTC). mMTC and URLLC scenarios, each having their requirements, are main categories of Machine-Type Communication (MTC) scenario. The channel coding scheme needed for the 5G MTC is yet to be chosen. Hence, this thesis contributes to filling knowledge and practical gaps in the area of finding the most appropriate channel coding for both 5G MTC scenarios. This thesis selects, investigates and assesses the following channel coding schemes: Low-Density Parity-Check (LDPC), turbo, polar, systematic convolutional and non-systematic convolutional codes, with their design parameters (some outlined design parameters) for both 5G MTC scenarios. The method of this thesis is to uses the 5G MTC user requirements to investigate different channel coding schemes for different short length message transmission (64 ≤ k ≤ 1024 bits) with different code rates (1/4, 1/3, 1/2) on an Additive white Gaussian noise (AWGN) channel with Binary Phase-Shift Keying (BPSK) modulation. Then, it evaluates the performance of different channel coding schemes in the 5G MTC user requirements. A comprehensive assessment of five-different channel coding schemes for both 5G MTC scenarios is included. Results of the study would include decoder computational complexity, encoding and decoding computational latency, and reliability. Finally, the results are expected to lead towards determining the most appropriate channel coding schemes for both 5G MTC scenarios. The evaluation of results shows that Systematic Convolutional Code (SCC) scheme is the most appropriate channel coding scheme for the 5G MTC scenarios in transmitting short length messages (k ≤ 1024 bits). Both Non-Systematic Convolutional Code (NSCC) and SCC satisfy the 5G MTC user requirements. NSCC scheme has a lower decoder computational complexity (8192 1.311 ×105) than SCC scheme, but the SCC scheme has high-reliability of 10−5 to 10−7 with 1 to 2 dB channel gain compared to NSCC scheme at the cost of small decoding computational latency difference of 2.062 ×10−4 - 1.398×10−3 second.